Allele-specific antibodies to Plasmodium falciparum merozoite surface protein-2 and protection against clinical malaria. - Osier, F; Murungi, L; Fegan, G; Tuju, J; Tetteh, K; Bull, P; Conway, D; Marsh, K (2010)
IgG and IgG3 antibodies to merozoite surface protein-2 (MSP-2) of Plasmodium falciparum have been associated with protection from clinical malaria in independent studies. We determined whether this protection was allele-specific by testing whether children who developed clinical malaria lacked IgG/IgG3 antibodies specific to the dominant msp2 parasite genotypes detected during clinical episodes. We analysed pre-existing IgG and IgG1/IgG3 antibodies to antigens representing the major dimorphic types of MSP-2 by ELISA. We used quantitative real-time PCR to determine the dominant msp2 alleles in parasites detected in clinical episodes. Over half (55%, 80/146) of infections contained both allelic types. Single or dominant IC1- and FC27-like alleles were detected in 46% and 42% of infections respectively, and both types were equally dominant in 12%. High levels of IgG/IgG3 antibodies to the FC27-like antigen were not significantly associated with a lower likelihood of clinical episodes caused by parasites bearing FC27-like compared to IC1-like alleles, and vice versa for IgG/IgG3 antibodies to the IC1-like antigen. These findings were supported by competition ELISAs which demonstrated the presence of IgG antibodies to allele-specific epitopes within both antigens. Thus, even for this well-studied antigen, the importance of an allele-specific component of naturally acquired protective immunity to malaria remains to be confirmed.